Measurement of nitric oxide in hippocampal slices: Induction with nitroso compounds and the effect of depolarization - (:unkn) unknown (My University, 2003)
Nitric oxide not only acts as a messenger for different physiological processes, but also mediates neurotoxicity associated with a variety of neurological disorders including epilepsy. The molecular mechanisms behind these actions are unclear. In this study, we aimed to detect relative amounts of NO released from rat hippocampal slices by chemiluminescence measurements under NMDA stimulation and spontaneous depolarization conditions. Hippocampal slices were preferred because of their functional integrity useful in simulating in vivo conditions. The reliability of the system was verified by administering increasing concentrations of a NO donor sodium nitroprusside in different redox milieu and a NO scavenger, carboxy-2-phenyl-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide (carboxy PTIO). The redox versatility of NO allows interconversion from neuroprotective to neurotoxic species by a change in the ambient redox milieu. We have quantitated NO formed under NMDA stimulation and spontaneous depolarization conditions, and showed that depolarization increased NO formation and was excitotoxic for the neural tissue.
Keywords: Chemiluminescence; Depolarization; Epilepsy; Hippocampal slices; Nitric oxide; Superoxide radical